2021
DOI: 10.3390/life11090979
|View full text |Cite
|
Sign up to set email alerts
|

Declining Mortality Rate of Hospitalised Patients in the Second Wave of the COVID-19 Epidemics in Italy: Risk Factors and the Age-Specific Patterns

Abstract: Background: Mortality rate from COVID-19 in Italy is among the world’s highest. We aimed to ascertain whether there was any reduction of in-hospital mortality in patients hospitalised for COVID-19 in the second-wave period (October 2020–January 2021) compared to the first one (February–May 2020); further, we verified whether there were clusters of hospitalised patients who particularly benefitted from reduced mortality rate. Methods: Data collected related to in-patients’ demographics, clinical, laboratory, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
4
6
0
Order By: Relevance
“…In line with the findings of two previous Italian studies [ 31 , 32 ], we also observed a trend towards a reduction in the proportion of critically ill patients upon admission between W1 and W3 (from 25.1% to 22.1% and then 17.6%). This change may have been due to increased access to COVID-19 testing and the detection of cases generally associated with a lower risk of death (testing was initially restricted to the most severely ill patients).…”
Section: Discussionsupporting
confidence: 92%
“…In line with the findings of two previous Italian studies [ 31 , 32 ], we also observed a trend towards a reduction in the proportion of critically ill patients upon admission between W1 and W3 (from 25.1% to 22.1% and then 17.6%). This change may have been due to increased access to COVID-19 testing and the detection of cases generally associated with a lower risk of death (testing was initially restricted to the most severely ill patients).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the ratio of direct deaths caused by COVID-19 tended to decrease in phase II, where most patients died due to severe comorbidities. This observation is equivalent to that reported in several official releases of epidemiological data and clinical reports (4,15,17,20,(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 86%
“…Mortality owing to COVID-19 has been linked to advanced age and concomitant chronic illnesses, which have been identified as the most significant risk factors [ 39 , 40 ]. In addition, the elderly and those suffering from chronic illnesses are at a higher risk of acquiring the condition [ 41 ]. Individuals with chronic illnesses have higher levels of anxiety (cardiovascular diseases, p < 0.001; metabolic conditions, p < 0.001; pulmonary conditions, p = 0.020; gastrointestinal conditions, p < 0.001), stress (cardiovascular diseases, p < 0.001; gastrointestinal conditions, p = 0.021), and poor resilience (cardiovascular diseases, p < 0.001; metabolic conditions, p = 0.037; gastrointestinal conditions, p = 0.024), which are all results that run parallel to one another.…”
Section: Discussionmentioning
confidence: 99%